The Influence of The Use of Artificial Intelligence (AI) and Digital Literacy on the Critical Thinking Skills of MPLB Students at SMK Negeri 42 Jakarta - Nadiyah, Nadiyah; Marsofiyati, Marsofiyati; Wolor, Christian Wiradendi (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2025)
This study aims to determine and analyze the effect of artificial intelligence (AI) and digital literacy on the critical thinking skills of MPLB students at SMK Negeri 42 Jakarta. The study was conducted using a quantitative method with a Likert scale questionnaire. The sample was selected using proportional sampling with a population of 144 students and a sample of 106 students. Data management and analysis were conducted using the IBM SPSS Statistics 22 software application, employing multiple linear regression analysis. The results of the data analysis indicate that: (1) the use of artificial intelligence (AI) has an effect on critical thinking skills with a significance level of 0.004 < 0.05; (2) digital literacy influences critical thinking ability with a significance value of 0.000 < 0.05; (3) simultaneously, the use of artificial intelligence (AI) and digital literacy influences critical thinking ability with an R2 value of 37%. The results of this study indicate that the proper and wise use of artificial intelligence can serve as an analytical and reflective tool in facilitating critical thinking processes among students. Digital literacy is an important foundation in shaping students to become analytical, reflective, and capable of facing information challenges. Therefore, support from various parties is needed to help students improve their critical thinking skills in facing the complex technological era.